Trends in the use of older overactive bladder agents and uptake of fesoterodine and mirabegron in Canada. Issue 5 (23rd April 2018) - Minhas, Rajwant; Tadrous, Mina; Elterman, Dean; Gomes, Tara
Abstract : Aims: To examine early trends in the use of overactive bladder (OAB) agents across Canada, with a focus on initial uptake and reimbursement of two newer agents: fesoterodine, an anticholinergic, and mirabegron, a therapeutically novel beta‐3 agonist. Methods: We conducted a population‐based cross‐sectional study of outpatient prescriptions for long‐acting oral OAB agents dispensed to individuals in Canada between May 2010 and April 2015 to examine the differences in the uptake of the newer agents and their reimbursement through cash, private, and public payers. Results: The national dispensing rate of OAB agents increased by 60% from May 2010 to April 2015 (from 924 to 1475 units per 10 000). We observed an increase in the dispensing rate of fesoterodine, solifenacin, and mirabegron, but a decrease in that of tolterodine and oxybutynin. Mirabegron was adopted rapidly after Health Canada approval, growing to a rate of 191 units per 10 000 by study completion, with its uptake being primarily funded through private payers (72.2%). Conversely, fesoterodine's uptake was minimal (8.3 units per 10 000) prior to its listing on public plans. This increased to 185 units per 10 000 by study completion, with the majority (65%) paid for by public insurers. Conclusions: The differences in the uptake and reimbursement of two new OAB agents emphasize the impact of therapeutically novel agents on the prescription rates of older OAB agents with significant adverse effects. Further studies are needed to explain changes in the dispensing rates as more provinces list the newer drugs on their formulary.